A magnetic study of a layered lanthanide hydroxide family: Ln8(OH)20Cl4·nH2O (Ln = Tb, Ho, Er). Issue 45 (2nd November 2018) - Coutinho, Joana T.; Pereira, Claudia C. L.; Marçalo, Joaquim; Baldoví, José J.; Almeida, Manuel; Monteiro, Bernardo; Pereira, Laura C. J.
Abstract : Experimental and semi-empirical calculations allowed the correlation of Ln electronic configurations and the diversity of different magnetic behaviors of these LLHs. Abstract : Three layered lanthanide hydroxides (LLHs), with the general formula Ln8 (OH)20 Cl4 · n H2 O (Ln = Tb (1 ), Ho (2 ), Er (3 )), were prepared and magnetically characterized both as pure compounds and diluted within a yttrium diamagnetic matrix, LYH :  x Ln, LYH : 0.044Tb (1′ ), LYH : 0.045Ho (2′ ), and LYH : 0.065Er (3′ ). This study was complemented with theoretical calculations in order to understand the electronic configuration and the contributions to the slow relaxation behavior. In the pure compounds dominant 3D ferromagnetic interactions are observed, with a small magnetization hysteresis at 1.8 K for1, while the magnetically diluted solid solutions display slow relaxation of magnetization at low temperatures.